2022
DOI: 10.1002/pen.25934
|View full text |Cite
|
Sign up to set email alerts
|

High antibacterial activity of new eco‐friendly and biocompatible polyurethane nanocomposites based on Fe3O4/Ag and starch moieties

Abstract: Control of microbial infections is one of the growing concerns in modern societies due to the increasing presence and risk of pathogenic bacterial spread. Therefore, there is a strong demand to design new antibacterial agents to overcome these problems. The aim of this study is the preparation of a new series of biocompatible starch‐based polyurethane (PU) nanocomposites with a unique combination of magnetic nanoparticles (MNPs) and silver nanoparticles (AgNPs). In order to perform the study, first, a new synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 89 publications
(169 reference statements)
1
21
0
Order By: Relevance
“…A new series of biocompatible starch‐based polyurethane (PU) nanocomposites were prepared by adding magnetic nanoparticles (MNPs) and silver nanoparticles (AgNPs), and the antibacterial activity was studied. [ 36 ] Antimicrobial properties of functionalized PVC samples and PVC interacted with thiazoles antimicrobial properties against Gram+, Gram‐, and Candida albicans were investigated. The antibacterial activity of the examined samples showed that all of the samples had a stronger inhibitory effect against the tested microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…A new series of biocompatible starch‐based polyurethane (PU) nanocomposites were prepared by adding magnetic nanoparticles (MNPs) and silver nanoparticles (AgNPs), and the antibacterial activity was studied. [ 36 ] Antimicrobial properties of functionalized PVC samples and PVC interacted with thiazoles antimicrobial properties against Gram+, Gram‐, and Candida albicans were investigated. The antibacterial activity of the examined samples showed that all of the samples had a stronger inhibitory effect against the tested microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it is difficult for oxidized starch adhesive to satisfy people's demand for wood products. In order to solve this problem, people use highly active chemical reagents or resins as hydroxyl crosslinking agents to modify starch, such as vinyl acetate, 16 furfural, 17 isocyanate, 18 and so on. The cross‐linked modified starch can bond hydroxyl groups between starches to form a three‐dimensional structure, enhancing the bonding strength of starch adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…Several metal oxide nanoparticles have been reported for their potential antibacterial activities against Gramnegative and Gram-positive bacteria, consisting of Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. These metal oxide nanoparticles include Al 2 O 3 (Jawad et al 2021;Karimi et al 2021), CuO, Cu 2 O, ZnO (Asamoah et al 2020;Karuppannan et al 2021;Han et al 2022;Khosravi et al 2022), CaO (Abbas and Aadim 2022), MnO 2 , MgO (Ogunyemi et al 2020;Amrulloh et al 2021), TiO 2 (Wang et al 2020;Zhang et al 2021), Fe 3 O 4 (Azizabadi et al 2021;Kamali et al 2022), Ag 2 O (Rashidi Ranjbar et al 2020;Dharmaraj et al 2021;Mahlambi and Moloto 2022), NiO (Kannan et al 2020;Christy et al 2021), and SiO 2 (Attallah et al 2022;Tran et al 2023). The antibacterial activity lies in its physical and chemical properties, which include morphology, chemical composition, particle size, surface characteristics, solubility, crystallinity, aggregation, and crystal phase.…”
Section: Introductionmentioning
confidence: 99%